If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 2 = 4 Reorder the terms: 2 + c = 4 Solving 2 + c = 4 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + c = 4 + -2 Combine like terms: 2 + -2 = 0 0 + c = 4 + -2 c = 4 + -2 Combine like terms: 4 + -2 = 2 c = 2 Simplifying c = 2
| 0.375-0.2=3.55 | | -7.32+9.91y-2.57-9.72y= | | 12(x+8)=11x-5 | | 2x=5y+2 | | 3x(x+7.1)(x-8)=0 | | 2w+5=30 | | 1/3(x-10)=-2/3(x+8) | | z^4-7z^2-144=0 | | 1-9x=-80 | | 2/3x+11=25 | | 2x-12+5s=4s-12 | | 1.1+x/3=-10.7 | | -4c+6=-42 | | 5g=4+(2g+2) | | 4q+5=15 | | 17=30x+5 | | k/5+4=18 | | 4n+2/5=-6 | | 5h-17=18 | | 14-7w=-4(3w+9) | | 8x^2=2x-3 | | (x+3)/2+15 | | 2g+9=17 | | -8x+2x=24 | | f/2-7=5 | | x+3/2+15 | | y/3-3=-6 | | 5k+18=7+3k-3 | | 4e+3=11 | | x+3/2 | | 3y=9x+2 | | 28=5x+8 |